Salve suas forças: a dialética-crioula e a análise do tempo aberto da colonialidade, uma aposta na potência da vida - Veloso, Aline Matheus (2022)
This work proposes to bring contributions to the various analyzes about coloniality, from the perspective of finding concrete ways of transforming this reality. Assuming, mainly, the concept of time of African peoples - based on Leda Maria Martins’ discussions about spiral time -, as well as a different conception of the body, it is argued that coloniality is constituted as a opened time by colonization that has not yet sealed, responsible for the hijacking of the human possibility of thinking about themselves and the world in a complex way. The investigations throughout the research reveals that, due to the epistemological and civilizing set of the African continent, Africa cannot occupy the place of anti-thesis in dialectical analyzes of reality. This understanding allowed the birth of what I call in this thesis as Creoledialectic, marked by the relationship between theses and their unpredictable syntheses, under which contradictions are not necessarily denied, but affirm the plurality of life's existence. Far from denying the dominations and genocides operated in this historical time, the Creoledialectic understands that the negation between the contradictions beings depend, decisively, on the modes of composition of the theses in relation, instituting the modes of bond, as a great terrain of understanding reality. From some African epistemological assumptions that underlie the Creole-dialectic, this work discusses the ways of internalizing this historical time, as well as its dynamics and expressions, in a link between mind and body, also understood as theses in relation, guided by the relationship slave-master. In this sense, the thesis is developed as having as its main source of information the narrative of adolescents in socioeducational measures, but also includes experiences in the clinical context of professional practice. From these sources, the consequences of this historical time in the support of individual and collective life are analyzed, as well as traces paths in order to guide a praxis that, through the recomposition of the gesture prior to captivity, contributes to sealing the colonial time, opening a new sun to guide us